Efektivitas Instrusion Detection System Pada Proxy Server XYZ dalam Mencegah Scanning Port oleh Hacker - Imam Asrowardi; Eko Subyantoro (Jurnal Ilmiah ESAI, 2014)
Due to its crucial role, a proxy server needs to be well maintained to ensure its appropriate functions. One of the causes of failure access in proxy server is data manipulation done by irresponsible users that work by scanning, gaining access, maintaining access and covering track. The scanning process appears as an important step as it exposes the types of applications and services utilized in the server. The step is to manipulate four vulnerable points of proxy server related to the operating system, applications, program modules and configurations. In order to prevent the scanning process, it is important to utilize a mechanism which is able to detect and report any indications of intruding access in the proxy server aka intrusion detection system. This research is aimed at producing an application operated in the proxy server to report any indication of access intrusion. The research uses System Development Life Cycle (SDLC) method by applying analyzing, designing, implementing and assessing.Key words: proxy, server, ids, scanning